Characterization of traditionally-prepared Valenzuela's Putong Polo (Polo rice cake) - Del Castillo, Kevin Samonte; Gonzales, Benjamin A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
A mixed methods research was conducted to assess the history, quality, and sensory attributes of putong Polo, a regional rice-based traditional delicacy from Valenzuela City, Philippines. Physicochemical (color, pH, water activity, moisture content, compressibility, and dimensions), microbiological (APC, YMC, and S. aureus), and sensory (acceptability and intensity) tests were employed, as well as interviews and focus groups. Narrative reports had traced the origins of putong Polo to an award given in the 1930's to the Nieva clan business, and explained that the product were confined to Polo Market and Valenzuela. Traditional methods were gathered from two well-known puto makers, "Mang Delfin's" (D) and "Rene's" (R), and were considered in formulating variant F. Variants were significantly different (p < 0.05) in *a, *b, and compressibility values while no significant difference was found for moisture content (32.31%-47.41%WB). The products was observed to be low-acid (6.67-7.56) and have relatively high water activity (0.89-0.91). Variant R had the highest aerobic, yeast and mold, and S. aureus counts (6.36, 4.82, and 5.04 log cfu/g, respectively), and failed most of the standards for comparison. The range of microbial loads for APC, YMC, and S. aureus for variant R were 6.31-6.41, 4.23-5.42, and 3.12-6.95 log cfu/g, respectively. Variant D and F (4.27-4.95, 2.88-3.82, and 2.48-3.91 cfu/g for APC, YMC, and S. aureus, respectively) were similar in microbial load. Consumer sensory evaluation (n=30) showed variant D was the most liked sample, and was significantly different with the other commercial brand. The results for variant F showed that it was within the consumer acceptability of the market variants. Color intensity, as tested by consumers, was found to be significantly varying among the samples while cooked rice flavor and springiness (tactile and oral) were not. Taste and oral texture (graininess) were the prime attributes to be considered for overall consumer acceptance. The focus groups (n=2) consistently described putong Polo as: malambot (soft), malagkit (sticky), mabango (aromatic), matamis (sweet), maliit (small), and bilugan (roundish). The groups qualitatively explored some attribute relationships (color and graininess) observed during quantitative testing. Insights on the shelf life and progress of the product were also gathered. Recommendations include further studies in shelf-life stability and optimization, as well as assessing other physicochemical and microbial parameters. The holistic approach used in the characterization research presents an opportunity for a unique understanding of Philippine traditional food products, thus, promoting progress through further commercialization and innovation.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Rice cakes -- Philippines -- Valenzuela City (Metro Manila).; Rice products -- Philippines -- Valenzuela City (Metro Manila).